The Dynamics Existence of Renege Group Ahad Sunnah in Indonesia - Mufasiroh Mufasiroh (Religia, 2021)
The validity between mutawatir and ahad Sunnah is debated in the era after sahabat and the era after that. Some groups reject the existence of Sunnah, both ahad and mutawatir as a whole, while other groups do not accept the ahad Sunnah to be used as a source in establishing the law. This group is known as inkar al-sunnah. The phenomenon of the existence of the sunnah group also exists in Indonesia. The author tries to analyze a group that rejects the ahad Sunnah in determining the source of law by using a qualitative method with a content analysis approach to this concept. The results of the study explain the principle of reneging the sunnah group, which considers the Qur'an to be a qath'i guide that has a complete source, explaining things in detail about everything until it does not need sources from things like dzann and ahad Sunnah. Three categories of groups reject the Sunnah. First, some groups reject the Sunnah altogether; Second, some people reject the Sunnah unless it has an empirical correlation with the instructions contained in the Qur'an; and Third is a group who does not accept the ahad sunnah. The third group is incorporated in various groups, including Mu'tazilah and Orientalists. In general, there are several principles of doctrine in reneging sunnah Indonesian. It consists of not admitting two sentences of the creed. Do not admit the perform five daily prayers and the iqamat call to prayer every time. Do not admit the existence of Eid al-Fitr, Eid al-Adha, and tarawih prayers; Eliminate congregational prayers every time. Then, there is no obligation to fast in Ramadan, zakat fitrah, and Friday prayers; the dead people may not be bathed, shrouded, and prayed. Allah and the Messenger are united (dual single) following the forbidden Prophet Hadith. Prophet Muhammad does not deserve to explain a religion that destroys the member of a religious community.